Improving Zero Knowledge in Cloud Storage Auditing System - B. Subasri; P. Vijayalakshmi; P. Yurega; E. Revathi (International Journal of Computer Sciences and Engineering, 2014)
Usage of cloud storage user can store the data tenuously and have the benefit of on demand high quality applications and services from a shared pool of configurable computing resources without the burden of local data storage and maintenance. Utilize the random masking to guarantee that the EA would not learn any knowledge about the data content stored on the cloud server during the efficient auditing process, which not only eliminates the burden of cloud user from the tedious and possibly expensive auditing task, but also alleviates the usersï¿½ fear of their outsourced data leakage